2017
DOI: 10.3892/or.2017.5918
|View full text |Cite
|
Sign up to set email alerts
|

Killing effect of methionine enkephalin on melanoma in vivo and in vitro

Abstract: Melanoma is a common cutaneous malignancy, that is also found in specific mucosal sites, and is associated with a poor prognosis. The aim of the present study was to investigate the cytotoxicity of methionine enkephalin (MENK) for B16 melanoma cells in vivo and in vitro. The results of the present study allowed our conclusion that MENK regulates the proliferation of B16 cells, causing cell cycle arrest in the G0/G1 phase and a decrease in the percentage of cells in the S and G2/M phases. Reverse transcription-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Although AMPs have been shown to act by a variety of diverse mechanisms, both within the membrane and in the cytoplasm and cell nucleus ( Graf and Wilson, 2019 ; Haney et al, 2019 ; Zasloff, 2019 ), all AMPs, as positively charged amphipathic molecules are initially targeted to the cell membrane through electrostatic interactions. Some AMPs can exploit both differences in membrane charge and cell stability to specifically target certain cancer cells ( Rathinakumar et al, 2009 ; Mahlapuu et al, 2016 ; Wang et al, 2017 ), suggesting that these peptides are potential new anti-cancer agents and encouraging the further development of other classes of AMPs in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AMPs have been shown to act by a variety of diverse mechanisms, both within the membrane and in the cytoplasm and cell nucleus ( Graf and Wilson, 2019 ; Haney et al, 2019 ; Zasloff, 2019 ), all AMPs, as positively charged amphipathic molecules are initially targeted to the cell membrane through electrostatic interactions. Some AMPs can exploit both differences in membrane charge and cell stability to specifically target certain cancer cells ( Rathinakumar et al, 2009 ; Mahlapuu et al, 2016 ; Wang et al, 2017 ), suggesting that these peptides are potential new anti-cancer agents and encouraging the further development of other classes of AMPs in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Some AMPs can exploit both differences in membrane charge and cell stability to specifically target certain cancer cells ( Rathinakumar et al, 2009 ; Mahlapuu et al, 2016 ; Wang et al, 2017 ), suggesting that these peptides are potential new anti-cancer agents and encouraging further development of other classes of AMPs in this area. When examining the effects of Smp24 and Smp43 in morphological studies ( Elrayess et al, 2019 ), we found suggestive evidence of pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that OP regulate NKCA [17,42]. NK cells have generated increasing interest due to their potential role in hematopoiesis and in the control of viral infections, as well as in the growth of some types of tumors and in the extracellular destruction of bacteria [43,44]. Although several agents capable of positively or negatively altering NKCA have been described, the mechanism by which this process develops is not completely clear.…”
Section: Discussionmentioning
confidence: 99%
“…similar in both cases studied. On the other hand, when the lymphocytes were treated with concentrations higher than the physiological ones, a response greater than 25% of the control value was obtained, even though this stimulation is not present in the total of the samples analyzed and no dependence was observed on the age or sex of the individual studied Probably the individual diversity of the samples as well as to the high heterogeneity existing in the NK cells, since it has been described that they form at least three subpopulations of functionally distinct cells: effector cells capable of binding and destroying the target cell and two non-cytolytic subpopulations, one capable and the other incapable of joining the target cell [43,51]. Our results and the fact that Naloxone inhibits the increase in NKCA mediated by both IL-2 and IFN-α [47,52] it would be expected to have the existence of opioid receptors in NK cells, both due to the stimulation achieved as per the relationship between OP and Naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recorded growth restriction after the application of 50 µg of MENK for 1–2 weeks, which was countered by naloxone, confirming the opioid receptor involvement [ 283 ]; these effects were obtained via both direct cytotoxicity on melanoma cells as well as through immune response modulation. Using the same animal model, Wang et al have identified that MENK augments OGFr expression, causes cell cycle arrest, and increases the ratio of CD4+/CD8+ T cells as well as plasma levels of various cytokines including IL-2, TNF-α, and interferon-γ [ 284 ]. These effects increase survival while limiting tumor growth and dissemination.…”
Section: Neuropeptides and Melanomamentioning
confidence: 99%